Prevalence of risk factors for non-communicable diseases in prison populations worldwide: A systematic review - Herbert, K; Plugge, E; Foster, C; Doll, H (2012)
The burden of non-communicable diseases (NCDs) is disproportionately carried by low-income and middle-income countries and disadvantaged sectors of society such as prisoners. No systematic analysis has been done to assess the prevalence of poor diet, inadequate physical activity, and overweight and obesity in prisoners. We aim to synthesise current evidence and to highlight areas for action and further research. Methods We systematically searched online databases for reports published between 1948 and May, 2011. Studies were screened against eligibility criteria; two authors then independently extracted data with previously agreed proformas. The risk of bias was assessed for each study with a domain-based assessment. Data on body-mass index and physical activity were presented in forest plots; no overall estimates were calculated on account of data heterogeneity. Available data from the population subgroup most similar in terms of age and sex were used to calculate age-adjusted and sex-adjusted prevalence ratios, which estimate the likelihood of insuffi cient activity and obesity prevalence in prisoners compared with the national population. Findings 31 eligible studies were reported in 29 publications, including more than 60 000 prisoners in 884 institutions in 15 countries. Male prisoners were less likely to be obese than males in the general population (prevalence ratios ranged from 0·33 to 0·87) in all but one study (1·02, 0·92-1·07), whereas female prisoners were more likely to be obese than non-imprisoned women in the USA (1·18, 1·08-1·30) and Australia (prevalence ratios ranged from 1·15 to 1·20). Australian prisoners were more likely to achieve suffi cient activity levels than the general population compared with prisoners in the UK (prevalence ratio 1·19, 95% CI 1·04-1·37, for women in Australia in 2009 vs 0·32, 0·21-0·47, for women in the UK; prevalence ratios ranged from 1·37 to 1·59 for men in Australia vs 0·71, 0·34-0·78, for men in the UK). Female mean energy intake exceeded recommended levels and sodium intake was about two to three times the recommended intake for all prisoners. Interpretation Contact with the criminal justice system is a public-health opportunity to promote health in this vulnerable population; the costs to the individual and to society of failing to do so are likely to be substantial. Improved monitoring and further research is essential to inform appropriate targeting of public health interventions.